THE RISK PERCEPTION OF TUBERCULOSIS INFECTED DIABETES MELLITUS PATIENTS - Bernadette Dian Novita; Steven Wiyono; Maria Yuliastuti; Lydia Ari Widyarini; Evelyn Ongkodjojo (The Indonesian Journal of Public Health, 2022)
Introduction: The number of people with Diabetes Mellitus (DM) increases from year to year. Indonesia is in the sixth highest rank globally for the number of people with DM. Moreover, the level of risk of DM suffering TB is higher. The consequences can be prolonged if not treated immediately. However, the dangers of DM should be the concern of everyone. A non-healthy lifestyle such as high consumption of fast food and a sedentary lifestyle has a negative impact. DM will be worsened and can even lead to various diseases, including blindness, heart disease, kidney failure, stroke, or even amputation. Methods: This research was conducted in East Java and assessed the correlation between behavior, perception, perceived behavior control, and social support so that people can be motivated to seek information about the risk of TB in DM patients. This comprehensive community-based research combines quantitative and qualitative using a cross-sectional method on people who had been diagnosed with diabetes mellitus for at least one year. Information gathered concerning things to know for prevention and the desire to do the prevention. Result: The result of this research is the establishment of a brief video animation explaining the risk of TB in DM patients. Based upon data processing, DM patients diagnosed under five years are more active in seeking information about diabetes mellitus and its complications, including tuberculosis, as seen in table 3. Conclusion: The information is at their most plentiful access from social media (Facebook, Instagram), followed by radio, newspapers, television, and WhatsApp/ Line. Even more surprising, from the result of this research, it was found that the role of doctors or nurses was in the bottom two in providing information related to the risk of DM and TB. Similarly, health facilities (public health services, hospitals, clinics) are the third bottom after doctors and nurses. Of course, this is very unfortunate because the transfer of information from the primary source, in this case, health workers, did not occur properly. Keywords: Diabetes Mellitus; Tuberculosis; Perception; Risk of TB in DM Patients